Synthesis and characterization of volatile and thermally stable europium beta-diketonate complexes - Kang, SJ; Jung, YS; Sohn, YS (WILEY-V C H VERLAG GMBH, 1997)
Preparation and properties of Eu(hfa)(3) . L (Hhfa=hexafluoroacetylacetone, L=bis(2-methoxyethyl)ether, diglyme, and 2,2':6',2 ''-terpyridine, tpy), which are potential CVD precursors for europium, were investigated. The reaction of the Eu2O3 with Hhfa in the presence of tridentate neutral ligand yielded the nine-coordinated Eu(hfa)(3) . L. Eu(hfa)(3) . diglyme is air- and moisture-stable and most importantly has good volatility and thermal stability. Eu(hfa)(3) . tpy shows no sublime intact. The complex Eu(hfa)(3) . diglyme has been characterized by an X-ray structure determination; monoclinic P2(1)/n, a=10.252(1), b=16.051(6), c=19.392(8) Angstrom, beta=96.10(2)degrees, V=3173(2) Angstrom(3). The europium atom in Eu(hfa)(3) . diglyme adopts a square-antiprismatic geometry with the ninth coordinating oxygen atom capping one of the square faces. All the adducts have been characterized by IR, TGA/DTA.
Keywords: CRYSTAL-CHEMISTRY; GLYME COMPLEXES; SUPERCONDUCTIVITY; PRECURSORS; MOCVD; YTTRIUM